Reciprocal developmental regulation of presynaptic ionotropic receptors - Turecek, Rostislav (The National Academy of Sciences, 2002)
Activation of ionotropic glycine receptors potentiates glutamate release in mature calyceal nerve terminals of the rat medial nucleus of the trapezoid body, an auditory brainstem nucleus. In young rats, glycine and its receptors are poorly expressed. We therefore asked whether GABA (γ-aminobutyric acid) might play a larger role than glycine in the regulation of glutamate release in the absence of glycine receptors. Indeed, in rats younger than postnatal day 11 (P11), and before the onset of hearing, calyces expressed high levels of ionotropic GABA(A) receptors but few glycine receptors. Isoguvacine, a selective agonist at GABA(A) receptors, strongly enhanced excitatory postsynaptic currents in young rats but had little effect in rats older than P11. Down-regulation of presynaptic GABA(A) receptors did not reflect global changes in receptor expression, because the magnitude of GABA and glycine responses was similar at P13 in the parent-cell bodies of the calyces, the bushy cells of the cochlear nucleus. In outside-out patches excised from the nonsynaptic face of calyces, GABA and glycine evoked single-channel currents consistent with the properties of postsynaptic GABA(A) and glycine receptors. Inhibitory GABA(B) receptors were present on the calyx at all developmental stages examined. Thus, GABA initially acts on two receptor subtypes, both promoting and inhibiting glutamate release. With age, the former role is transferred to the glycine receptor during the period in which postsynaptic glycinergic transmission is acquired.